Overexpression of IGF2 affects mouse weight and glycolipid metabolism and IGF2 is positively related to macrosomia - Zhang, Qidi; Qin, Shengtang; Huai, Jing; Yang, Huixia; Wei, Yumei (Frontiers in Endocrinology, 2023)
To investigate the effects of insulin-like growth factor 2 (IGF2) on growth and glycolipid metabolism, as well as the underlying mechanism, a mouse model of IGF2 overexpression was constructed to measure weight gain before adulthood, obtain the values of adult glycolipid metabolism indicators in the peripheral blood and detect the expression of genes in the IGF2 signaling pathway in different mouse tissues. By detecting and comparing the expression levels of IGF2 mRNA/H19 RNA in maternal peripheral blood and fetal cord blood of 26 human pregnancies, the present study also explored the independent association between the IGF2 gene and macrosomia. The results of this study indicated that IGF2 expression was independently correlated with the occurrence of macrosomia, and overexpression of IGF2 significantly increased the weights of mice at the age of 5-10 weeks and significantly affected the values of adult glycolipid metabolism indicators, which might be the result of changes in the IGF2-IGF1R-STAT3/AKT2-GLUT2/GLUT4 pathway. These findings suggest that IGF2 plays an important role in growth and glycolipid metabolism during both pregnancy and postnatal development.